Use of nebulized milrinone in cardiac surgery; Comparison of vibrating mesh and simple jet nebulizers. (October 2017) - Gavra, Paul; Laflamme, Maxime; Denault, André Y.; Théoret, Yves; Perrault, Louis P.; Varin, France
Abstract: Cardiopulmonary bypass triggers an ischemia-reperfusion injury with endothelial dysfunction in the pulmonary circulation which can result in pulmonary hypertension. Inhaled milrinone reduces this reperfusion phenomenon and two methods commonly available for administering it are simple jet and vibrating mesh nebulizations. However, neither their generated milrinone particle size profiles, nor their ability to aid endothelial relaxation have been compared. Simple jet and vibrating mesh particle size distributions of milrinone were verified through cascade impaction and their efficacy was tested on a cardiopulmonary bypass (CPB) swine model. Post-nebulizations, animals underwent 90 min of CPB, followed by 60 min of reperfusion and lung excision. Pulmonary arterial endothelium-dependent relaxations to acetylcholine and bradykinin were then performed on pulmonary vasculature rings and were subsequently modeled as inhibitory Emax functions. In vitro studies showed lower emitted and inhaled doses from the simple jet nebulizer and its particle size distribution indicated upper and middle airway targeting. During in vivo studies, milrinone pre-treated, unlike saline groups maintained baseline pulmonary pressures up to 30 min post–CPB. Ex vivo studies showed better endothelial relaxation of arteries from the two milrinone groups over those from the control group in an administration/pathway-dependent manner, favoring simple jet administration.